Peran Kritis Tourist Engagement dalam Meningkatkan Revisit Intention Wisatawan Taman Mini Indonesia Indah - Amelia, Winda; Ernawadi, Yadi (J-MAS (Jurnal Manajemen dan Sains), 2024)
The aim of this research is to examine the influence of destination image, tourist engagement, and destination attributes on revisit intention through the memorable tourist experience of Taman Mini Indonesia Indah tourists. A total of 150 respondents who had experience visiting Taman Mini Indonesia Indah participated in this research. The cross-sectional or one shot method is used to obtain data. The research instrument has been declared to have passed the validity and reliability tests. The data analysis technique used is structural equation modeling (SEM) using Smart-PLS version 3.0. Of the ten proposed research hypotheses, nine of them have a positive influence. Destination image, tourist engagement, and destination attributes have a direct and indirect influence on revisit intention. The addition of destination attribute variables as a consequence of revisit intention is a development of the conceptual model in previous research.